How rural school teachers can support the learning adjustment of left‐behind children under the ‘double‐reduction’ policy - Xuedi Pi; Jianping Huang; Jiong Niu (Future in Educational Research)
AbstractQuality‐oriented education under the guidance of the ‘Double Reduction’ policy aims to ensure all children grow in an all‐around way with different backgrounds. However, many left‐behind children (LBC) whose parents work away in cities have a greater tendency toward academic and mental problems compared with non‐left‐behind children. Teachers are the important adults in the lives of the LBC who spend much time staying with each other. This study draws from interviews with 16 rural primary and secondary school teachers. Guided by social support theory, this qualitative research highlighted the importance of teacher support on children's learning adjustment through social support networks. It argued that strategic guidance of teachers targets individuals' difficulties in the environment through emotional support, material support, information support and companionship. Under the ‘Double Reduction’ policy, teachers adopted tiered instruction and offered after‐school services to meet the needs of LBC. Finally, the result revealed that rural teachers help LBC change their learning attitudes, thereby promoting self‐learning ability.